Revision of the Afrotropical genus Fernandea Melichar, 1912 (Hemiptera: Fulgoromorpha: Dictyopharidae), with description of a new species from Equatorial Guinea - Song, Zhi-Shun; Malenovský, Igor; Liang, Ai-Ping (Zootaxa, 2016)
The Afrotropical planthopper genus Fernandea Melichar, 1912 (Hemiptera: Fulgoromorpha: Dictyopharidae: Dictyopharinae: Orthopagini) is revised to include two species: F. conradti Melichar, 1912 (the type species), with material studied from Cameroon, Equatorial Guinea (Bioko island) and Togo, and F. latifemorata sp. nov., described as new from mainland Equatorial Guinea. A lectotype is designated and a redescription is provided for F. conradti together with habitus photographs and detailed illustrations of the male and female terminalia which are published for the first time.
Keywords: Animal Structures; Animal Distribution; zvířata; Male; Female; Equatorial Guinea; Kamerun; velikost orgánu; Heteroptera; anatomické struktury zvířat; Cameroon; Animals; mužské pohlaví; ženské pohlaví; Body Size; Rovníková Guinea; rozšíření zvířat; Organ Size; velikost těla